Proposing Parameters for Evaluating Sustainability of mHealth Systems in Developing Countries - Muhambe, Titus (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
The exponential rise in global healthcare challenges; the rise in morbidity and mortality, especially in developing countries have compelled stakeholders to explore alternative ways of overcoming the crisis. Guided by the recommendation of WHO (2013), efforts have been directed towards prevention, response and strengthening of the existing healthcare systems. There have also been efforts to explore the potential of mobile technology towards healthcare provision, with numerous mHealth projects being reported across the developing world. Reports indicate that a significant number of these solutions have failed before realizing the primary goals, pointing to a possible mHealth sustainability challenge. The study explored literature covering global health challenges, use of mobile technology healthcare solutions in developing countries as well literature covering evaluating technology sustainability. Through the review, key factors that influence sustainability of technology were identified. A cross-sectional survey using questionnaires and a qualitative exploratory study using interviews and Focused Group Discussion, targeting mHealth stakeholders were used to map and contextualize the identified sustainability factors to the developing country context. The identified factors were categorized into three broad categories; Individual factors; User Satisfactions, Access to system, and User Support, Technological Factors; System Quality, System Scalability, Technology Sustainability, Technology Relevance and System Interoperability and Management Factors; mHealth Ownership and Net Benefits (Return on Investment). The paper identifies challenges in the sustainability of mHealth systems in developing countries; using Kenya health sector as a case study and propose sustainability evaluation parameters for mHealth systems in developing countries.